Anatomic study of the arterial vascularization of the brain base of paca (Cuniculus paca) - Sasahara, Tais H.C.; Fontes, Vitória F.N.P.; Garcia, Débora O.; Rocha, Daniel W.; Oliveira, Fabrício S. [UNESP]; Leal, Leonardo M.; Machado, Marcia Rita F. [UNESP]; Dias, Fernanda G.G. (FapUNIFESP (SciELO), 2020)
Paca (Cuniculus paca Linnaeus, 1766), rodent belong to the Cuniculidae family, has encouraged numerous scientific researches and for this reason could be an experimental model in both human and veterinary areas. And recently, the economic exploitation of the meat cuts, has being direct implication in its zootechnical importance. However, no anatomical descriptions regarding the vascularization of the base of the brain in this rodent has being found. Thus, the aim of the present study was to describe the arteries and the pattern of the vasculature and to compare it with the other species already established in the literature. For this, five pacas, donated by the Unesp Jaboticabal Wildlife Sector, were euthanized followed by the vascular arterial system was injected with red-stained-centrifuged latex by the common carotid artery. After craniectomy, the brains were removed and the arteries were identified and, in addition, compared with those described in other animal species. The presence of the right and left vertebral arteries, close to the medulla oblongata, was detected, originating the basilar artery, which divided into the terminal branches of the right and left basilar artery. Ventral to the optic tract there was the right internal carotid artery and the left, dividing the middle cerebral artery and left rostral and right; dorsal to the optic chiasm, the medial branch of the rostral cerebral arteries was identified. Based on the results, it is concluded that the vascularization of the paca brain base is supplied by the carotid and vertebrobasilar system.
Keywords: Anatomy; Arterial circuity; Arterial vascularization; Brain; Brain base; Central nervous system; Cuniculus paca; Morphology; Paca; Rodent